Style Shift: A Comparative Cultural Analysis of Pride and Prejudice and Unmarriageable - Muhammad Ramzan; Dr. Misbah Afsheen Khan; Maria Sarwar (University of Chitral Journal of Linguistics and Literature, 2023)
The writing style is the core element of the authors as it varies from place to place under cultural representation through code-mixing and code-switching. The current study is qualitative in nature describing the style shift and the code mixing and code switching in the context of the non-native speakers. The study is being conducted comparatively on the analysis of two novels Pride and Prejudice by Jane Austen (1813) and Unmarriageable by Soniah Kamal (2019) to highlight the element of style shift from native to non-native context. The study concludes that the shift of the style and sense being presented in the native context of the English language is of a universal level while the style of non-natives is of local level with the inclusion of code-mixing and code-switching.